Analisis Unsur Intrinsik Dan Unsur Ekstrinsik Pada Pupuh Kinanti Dan Pupuh Balakbak - Iqbal Maulana Sidik; Sri Resti Sulistiawati; Nurul Hikmah; Herliana Herliana (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
Sundanese culture is one of Indonesia's rich and unique cultures. Sundanese culture is known as a culture that upholds high manners. Sundanese has very diverse arts, for example pupuh, pupuh can be categorized as one of the Sundanese arts. Pupuh is an inseparable part of Sundanese tradition and culture, so preserving it means preserving cultural heritage. Pupuh is also a traditional poetic work in Sundanese literature that has characteristics that have certain rules such as the number of syllables (guru wilangan), the final sound of the word (guru lagu), and the number of lines (pada lisan) in each stanza. In addition, pupuh also has its own character or characteristics that distinguish it from one another. However, pupuh is not just written poetry. Pupuh is also often combined with music and dance. So that it becomes a complete art performance. Pupuh production involves creativity in word choice, rhyme and rhythm to convey a message. The themes raised in pupuh are very diverse, ranging from love, affection, life, daily life, to advice and moral teachings. Through pupuh, we can understand more about the history, customs and noble values of the Sundanese people.Pupuh kinanti and pupuh balakbak are pupuh in Sundanese literature. Pupuh kinanti is a pupuh known for its expression of affection. The characteristic of pupuh kinanti lies in its guru wilangan and guru lagunya. While pupuh balakbak is a pupuh that is more inclined to the theme of humor, satire, and even social criticism. The language used is more relaxed and straightforward, has a different guru song and guru wilangan from kinanti. The basic difference between pupuh kinanti and balakbak lies in the theme, atmosphere, and social function. Pupuh kinanti is more introspective and explores inner feelings while pupuh balakbak is more extroverted and functions as a means of entertainment.Besides being a form of self-expression, pupuh also has social functions such as education, entertainment, and cultural preservation. Pupuh has developed over time, both in terms of form and content. Pupuh is not only present in literary works, but also in the daily life of the Sundanese community, for example in folk songs or rhymes.